(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The present work is carried out in commercial shrimp farms located at Ampalam of Srikakulam District, Andhra Pradesh, India, over a period of two consecutive years i.e. 2018 2019. Modified extensive shrimp farms were selected for this research work. The data was recorded from both control and experimental ponds in summer and winter crops. In the present study the growth and survival of the shrimps in all the experimental ponds showed better performance than control ponds in two different crops during the study period. The important point of consideration in the study is that the application of feed probiotics along with the immunostimulant showed significantly better results than the feed probiotics alone given in the feeds to the shrimp. The slow growth rate in the control ponds in the selected study area was due to high pathogenic bacterial loads, delayed moulting and stunted growth.